What do unions do to pension performance? - William E. Even; David A. Macpherson (Institute for the Study of Labor (IZA), 2010)
This study argues that the promotion of union goals could have positive, negative, or neutral effects on risk adjusted return performance. Moreover, the union's ability and incentive to use pension assets to promote union goals will vary with the design of the pension. Using panel data on over 36,000 pension plans drawn from IRS Form 5500 filings, we empirically estimate the effects of unions on risk adjusted returns and find that the union effect on performance varies in ways that are consistent with our priors. In particular, unions have the largest negative effect among multi-employer defined contribution plans and the negative effect of unions can be eliminated by a switch to participant direction. Also, we find that unions improve performance for single employer defined contribution plans.
Keywords: J32; J51; 330; unions; rate of return; pension; defined benefit; defined contribution